Industrial Ecology Perspectives on Plastic Waste Valorization: A Systematic Literature Review of Industrial Symbiosis, Material Flow, and Circular Manufacturing - Rivasha Nirmala Viandar Putri; Melani Fera Ayulia; Monica Rumondang Panjaitan; Temmy Wikaningrum (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The global plastic waste crisis necessitates a paradigm shift from linear management approaches to systemic industrial transformation. This Systematic Literature Review (SLR) explores plastic waste valorization through the lens of Industrial Ecology (IE), moving beyond conventional recycling technologies to analyze broader systems-level changes. Following the PRISMA 2020 guidelines, we synthesized over 100 peer-reviewed articles published between 2022 and 2026. The review focuses on four pillars of IE: Industrial Symbiosis (IS), Material Flow Analysis (MFA), Industrial Metabolism, and Circular Manufacturing. Our findings reveal that while technical valorization pathways (e.g., PET upcycling to high-value chemicals) are advancing rapidly, their systemic integration remains fragmented across industrial sectors and geographic boundaries. MFA emerges as the primary diagnostic tool for identifying resource leakage points throughout the plastic life cycle, while IS networks facilitate multi-actor collaboration to close material loops through coordinated waste-to-resource exchanges. The results demonstrate that IE-driven strategies can reduce virgin polymer demand and greenhouse gas emissions by up to 40−88% compared to traditional disposal methods such as landfilling and incineration. However, significant research gaps remain in the standardization of resource efficiency indicators, the integration of diverse